Limit Pricing, Climate Policies, and Imperfect Substitution - Gerard C. van der Meijden; Cees A. Withagen (Center for Economic Studies and ifo Institute (CESifo), 2016)
The effects of climate policies are often studied under the assumption of perfectly competitive markets for fossil fuels. In this paper, we allow for monopolistic fossil fuel supply. We show that, if fossil and renewable energy sources are perfect substitutes, a phase will exist during which the monopolist chooses a limit pricing strategy. If limit pricing occurs from the beginning, a renewables subsidy increases initial extraction, whereas a carbon tax leaves initial extraction unaffected. However, if initially fossil fuels are cheaper than renewables, a renewables subsidy and a carbon tax lower initial extraction, contrary to the case of perfect competition. Both policy instruments lower cumulative extraction. If fossil fuels and renewables are imperfect but good substitutes, the monopolist will exhibit `limit pricing resembling' behavior, by keeping the effective price of fossil close to that of renewables for considerable time. The empirical question whether energy demand is elastic or inelastic has less drastic implications for the fossil price and extraction paths than under perfect substitutability.
Keywords: Q31; Q42; Q54; Q58; 330; limit pricing; non-renewable resource; monopoly; climate policies